If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(6-2x)+2=2-x
We move all terms to the left:
(6-2x)+2-(2-x)=0
We add all the numbers together, and all the variables
(-2x+6)-(-1x+2)+2=0
We get rid of parentheses
-2x+1x+6-2+2=0
We add all the numbers together, and all the variables
-1x+6=0
We move all terms containing x to the left, all other terms to the right
-x=-6
x=-6/-1
x=+6
| 4h=–6+2h | | x=35/27 | | x+2-0,5x=1+0.5x+1 | | 5(x+1)=4(x-1)-2x | | 1/6(p+24)=10 | | 20+x2=120 | | –5−5p=–10p | | 60x20=20x60 | | 4x-7=6x+5-x | | 4p=6(4p=5) | | 3x-4+2x-4x=6 | | 2u+5=4u+15 | | -8+5v=7v+10 | | -5x+4(3+2.5x)=8x+12-3 | | (2-1)=3=3x+1 | | 3+5x-8+13x=121 | | 50x+4=2 | | 250-2x=180+5x | | 50x-4=2 | | 14x-6-7x+10=-17 | | (5x-10)=50 | | 3x÷5+1=7÷10 | | 80+v+v=180 | | 48=6(5-3n)+6(6+4n) | | -8x+4+2x=16 | | 80=10(x-2) | | 14=⅓x+5;27 | | X-1=7x-5=180 | | 7+16y=11;¼ | | -8m+2+7m=6-5m | | 22=10-4x | | 18x/24-11x/24=-14/24 |